## pudding 3 years ago 5(2x-1) =4(x+3) solve the equation

1. zordoloom

Start by distributing both right side and left side.

2. rahul91

10x-5 = 4x+12 6x=17

3. rahul91

thats it

4. zordoloom

@rahul91 pretty much gave you the correct answer.

5. zzr0ck3r

we should not just give answers...

6. pudding

THNK U!! SO I DO DISTRIBUTIVE PROPERTY AND THEN I SUBRACT 4 ON BOTH SIDES?

7. Muskan

|dw:1350155690386:dw|

8. pudding

IT'S NO SOLUTION THEN?

9. rahul91

1st apply distributive property we get 10x-5=4x+12 group x terms to one side, when we take a number to otherside of equation (= sign ) change the sign of the number ie; 10x-4x=12+5 6x=17

10. pudding

yeah but u have to simplify it right? so x= 17/6

11. zordoloom

Yep. Exactly

12. rahul91

yes x= 17/6 ...atlast

13. rahul91

x is not unknown anymore :D

14. pudding

so u leave it as a fraction right? ahaha

15. rahul91

yep!

16. pudding

yayy thnk u so muchh!! :P

17. pudding

wooohooo i got a medalll xD i feel special ahha jkjk

18. rahul91

:)

19. pudding

wait i forgeot to put a negative 4 so it's like 5(2x-1)=-4(x+3) would that equal to x= -2??

20. zordoloom

no, x=-1/2

21. pudding

thnks u c: